Holistic Thinking and Proactive Decision-Making with Goal Commitment of Hotel Employees (Global Journal of Management and Business Research, 2022)
This study examines the relationships between holistic thinking, proactive decision-making, and organizational goal commitment in the context of hotel employees. Variables related to holistic decision- making include causality, attitude towards contradiction, perception of change, and locus of attention. Proactive decision-making considers objectives, the search for further information, alternatives, and decision radars. The hypotheses regarding the relationship among the variables were empirically tested with hotel employees. The results indicate that the hotel employees#x2019; causality, perception of change, and locus of attention were related positively to their organizational goal commitment while their attitude towards contradiction negatively influenced it. Furthermore, holistic thinking did not make a significant direct impact on proactive decision-making. In addition, goal commitment significantly influenced the seeking for more information and use of decision radar, while it failed to influence searching for objectives and alternatives. Finally, it was found that organizational goal commitment significantly mediates the relationship between holistic thinking and proactive decision-making.
Keywords: holistic thinking; proactive decision-making; organizational goal commitment; hotel employees; decision-making